Self-powered pressure sensor for detecting static and dynamic stimuli through electrochemical reactions. (March 2023) - Kim, Seonghyeon; Cho, Woosung; Hwang, Jeonghyeon; Kim, Joonwon
Abstract: As Internet of things (IoT) devices with pressure sensors become widely used, the need for lowering their power consumption increases. However, most pressure sensors require an additional power source to convert external stimuli into output signals. This study develops a self-powered pressure sensor (SPS) that measures both static and dynamic stimuli without an external power source. The SPS consists of two electrodes and a functional sponge with an electrolyte (water/glycerol/NaCl) and is based on an electrochemical reaction. The functional sponge is a hydrogel-coated polydimethylsiloxane (PDMS) sponge prepared by coating the surface of the PDMS sponge with a polyacrylamide (PAAM) hydrogel to contain the electrolyte. The SPS exhibits a sensitivity (10 kPa −1 ) and dynamic range (up to 110 kPa). The SPS is used on a self-powered safety alarm system to visually validate the pressure applied to the SPS. The SPSs are integrated into a glove to control an RC car using pressure applied to the SPSs on the fingertips. A thimble-type SPS is developed to measure the applied pressure and produce Morse code signals with static output signals. The SPS can be applied to wearable devices or robotics to measure pressure without an external energy source, reducing the system's energy consumption. Graphical Abstract: ga1 Highlights: A self-powered pressure sensor (SPS) is based on electrochemical reactions. The SPS can measure static and dynamic pressure stimuli without any external power source. The manufactured SPS is applied to a safety alarm system, wearable glove, and thimble-type SPS.